2019
DOI: 10.1002/sctm.19-0002
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Amniotic Fluid Stem Cell Therapy Protects Against Myelomeningocele via Spinal Cord Coverage and Hepatocyte Growth Factor Secretion

Abstract: Despite the poor prognosis associated with myelomeningocele (MMC), the options for prenatal treatments are still limited. Recently, fetal cellular therapy has become a new option for treating birth defects, although the therapeutic effects and mechanisms associated with such treatments remain unclear. The use of human amniotic fluid stem cells (hAFSCs) is ideal with respect to immunoreactivity and cell propagation. The prenatal diagnosis of MMC during early stages of pregnancy could allow for the ex vivo proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…4d ), and changes in TBX1 and ITGA1 protein levels were not significant. c-MET is the primary receptor of HGF, and HGF/c-MET signaling is involved in cell chemotactic migration and neuroprotection 17 , 37 . Thus, we determined HGF protein levels in both cultured BMSCs and developmental neural tubes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4d ), and changes in TBX1 and ITGA1 protein levels were not significant. c-MET is the primary receptor of HGF, and HGF/c-MET signaling is involved in cell chemotactic migration and neuroprotection 17 , 37 . Thus, we determined HGF protein levels in both cultured BMSCs and developmental neural tubes.…”
Section: Resultsmentioning
confidence: 99%
“…These studies demonstrated that after transamniotic injection, afMSC and pMSCs robustly migrated into the fetal bone marrow, placenta, umbilical cord, and spinal cord lesion 30 , 31 , 35 37 . Moreover, transplanted MSCs induced varying degrees of coverage of the defects through a membrane that appeared to be rudimentary skin based on histological analysis 32 , 37 . In turn, the coverage attenuated the Chiari-II malformation in rat fetuses with spina bifida 33 .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, AFSCs can also be used in prenatal therapeutic approaches through in utero transplantation (IUT); a strategy aimed at treating conditions such as congenital hematological diseases, spina bifida, and other neural tube defects. In our first Featured Article this month published in Stem Cells Translational Medicine , Abe et al establish the potential of human (h)AFSCs for the treatment of fetal myelomeningocele by demonstrating how administration via IUT reduced neural damage and promoted neural regeneration . In a Related Article published in Stem Cells , Loukogeorgakis et al demonstrated how IUT of in vitro‐expanded mouse AFSCs resulted in stable multilineage long‐term hematopoietic engraftment and, therefore, may represent an appealing approach to the treatment of inherited disorders of hematopoiesis .…”
mentioning
confidence: 99%